If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 = 10x + -7 Reorder the terms: 9 + 5x = 10x + -7 Reorder the terms: 9 + 5x = -7 + 10x Solving 9 + 5x = -7 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 9 + 5x + -10x = -7 + 10x + -10x Combine like terms: 5x + -10x = -5x 9 + -5x = -7 + 10x + -10x Combine like terms: 10x + -10x = 0 9 + -5x = -7 + 0 9 + -5x = -7 Add '-9' to each side of the equation. 9 + -9 + -5x = -7 + -9 Combine like terms: 9 + -9 = 0 0 + -5x = -7 + -9 -5x = -7 + -9 Combine like terms: -7 + -9 = -16 -5x = -16 Divide each side by '-5'. x = 3.2 Simplifying x = 3.2
| 5(x+4)-x=32 | | (4a+3)(a-1)=0 | | 18y=29x-52 | | -16.28=29.3-8.6y | | Y-1=2(x-2/3) | | 3x-(9x+5)=2x-37 | | 8m-20=12+6m | | 8.4y+9.77=-62.47 | | -21.32=3.2x+3 | | 3b^2-2=25 | | 8t+6-7t=6 | | 4x-30=7x-54 | | 6.6+1.7n=2.52 | | 5(2-4r)-3r=4r-287 | | 1.01(1.27)(9-x)=11 | | 4b=2b-1 | | 5.5y-6.1=19.20 | | b=3/4 | | 24(1.5+3)=n | | 8z(squared)=6z(squared)+38 | | x+27.3=8.9 | | m/-10=12=67 | | (7/10)/(5/16) | | 4x-5+2x+15=130 | | 4(3-5p)=9p-278 | | 2b+3=46-4 | | v^2+7=32 | | 4/9=x/11 | | 1.5+3=24 | | x-19=8x+2 | | -4y-15=-2y+5 | | 38(17-5.5x)=13(5x-9)+23.2 |